VD_FINDINFO Arrêt / 2012 / 765 vom 10. Januar 2013 - VD Tribunal cantonal (2013)
AIASSURANCE, NOUVELLE DEMANDE, REFUS D'ENTRER EN MATIÈRE SUR CERTAINS GRIEFS | 28 LAI, 4 LAI, 7 LPGA, 8 LPGA, 87 al. 3 RAI, 87 al. 4 RAI